EDITORIAL PREFACE (Volume 8, Issue 1, May 2020) - Pangaribuan, Christian Haposan (Journal of Business And Entrepreneurship, 2020)
Journal of Business and Entrepreneurship, Volume 8, Issue 1, May 2020.